DOMESTIC VIOLENCE IN THE JURISPRUDENCE OF THE EUROPEAN COURT OF HUMAN RIGHTS - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
This paper deals with the issue of the protection of persons from domestic violence in the jurisprudence of the European Court of Human Rights. It was not mentioned in the European Convention on Human Rights, but in the practice of the Court, there appeared a significant number of cases in which it stated that there had been violations of specific articles of the Convention in relation to domestic violence. In a large number of cases, the state did not prevent domestic violence that led to a violation of the right to life, or led to inhuman or degrading treatment. Also, domestic violence often leads to a violation of the right to respect for private and family life. The state is obliged to protect all persons under its jurisdiction when there is a reasonable suspicion that their rights may be violated. The Council of Europe’s Convention on Preventing and Combating Violence against Women and Domestic Violence is an important instrument that regulates this issue and is a step forward in the protection of victims of domestic violence.